Hypoglycemic and antioxidant activities of Morinda Citrifolia fruit in rats with diabetes mellitus induced by Aloxan - Nakamura, Carlos E. (2019)
The purpose of this investigation was to determine the hypoglycemic and antioxidant activities of the alcoholic extract of the fruit of Morinda citrifolia (noni), in normal rats and induced to type 2 diabetes mellitus by alloxan. For the Glucose Tolerance Test were used 56 rats were distributed into seven groups of eight each; one group without hyperglycemia induced and the remaining with hyperglycemia induced by glucose (750 mg/kg). To evaluate the action of the extract in rats induced with diabetes, we used seven groups of six animals each; one group without diabetes and the remaining with diabetes induced by alloxan (80 mg/kg). The determination of the antioxidant activity in vitro and in vivo was performed by the neutralization of the 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) and by measuring the levels of malondialdehyde (MDA) and nitric oxide (NO), respectively; finally was histopathological study of the pancreas. The results in the Glucose Tolerance Test were obtained significant results (p<0,05) at dose of 50 mg/kg; in the test with rats induced to diabetes had significant results (p<0,05) at doses of 50 and 150 mg/kg. The antioxidant activity was 33.74% at a concentration of 50 μg / mL and the levels of MDA (1.539 μmol / L) and NO (30.82 mmol / L) at a dose of 250 mg / kg were significantly decreased (p<0.05). The histopathological study demonstrated the protective action on the pancreas. It was concluded that the extract presented hypoglycemic and antioxidant activities in rats with type 2 diabetes mellitus induced by aloxane.